Developing a roadmap to reach and sustain 90% full immunization coverage through a cross-sectoral system strengthening strategy in Bihar, India - Manish Ratna; Sanjay Kumar Singh; Narendra Kumar Sinha; Mandar Kannure; Mehak Bhatia; Mahesh Kumar Aggarwal; Suresh Kumar Dalpath; Saurabh Sharma; Vama Shah (BMC, 2024)
Abstract Introduction Reducing childhood mortality by curtailing the incidence of vaccine preventable diseases is contingent upon a robust and high-performing routine immunization system. According to the available data, the full immunization coverage (FIC) in the state of Bihar (India) has reached ~ 71%. While the government aspires to reach 90% FIC, a systematic evidence-based investigation of the reasons behind underimmunization as well as the identification of drivers and enablers to reach and sustain 90% FIC is critical. This study aimed to review the factors leading to underimmunized children in the state of Bihar and develop a forward-looking roadmap to reach and sustain 90% FIC by adopting a system strengthening approach. Method We conducted a desk review, followed by extensive stakeholder interviews and field visits to document and analyze the data and evidence relevant to routine immunization system performance in the state of Bihar. The stakeholders included the State Immunization Officer, District Immunization Officers, Block-level health officials, representatives from development agencies, healthcare workers, and caregivers. A total of eighty-six structured interviews were conducted, which included qualitative and quantitative parameters. Result While positive results were observed from the assessment of Bihar's immunization system, the implementation of targeted strategies for supply, service delivery and demand can provide a means to achieve FIC of 90%. The roadmap developed by the Government of Bihar enlists 40 + interventions across key thematic areas and has been prioritized over a 5-year time horizon as short, medium, and long-term milestones to achieve 90% FIC. These interventions include strengthening the data availability and quality, improving the governance and review mechanism, augmenting the capacity of health workers involve with immunization programme, and initiatives to increase demand for immunization services. Conclusion The Bihar's Immunization Roadmap development project work follows a methodical approach to assess and identify intervention to improve immunization coverage and can provide information and reference to other states and countries that are aiming to formulate similar action plans.